HISTORY LEARNING IN INDONESIA DURING THE NEW ORDER - Umasih, - (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
The three dominant components in the implementation of historical learning are teachers, students and curriculum. The Curriculum function as a teacherâ€™s references to outline the learning and its implementation in the class. The initial is to develop a self-awareness in order that the students will embrace high-spirited nationalism that will be implied to their daily life as a national and global citizen.Â This article discuss on how the historical learning in High School implemented several curriculum in Indonesia. Thereforeurces data were obtained through research, observation, experince, and interview towards a number of history teachers from various of regions in Indonesia.